2023
DOI: 10.14336/ad.2023.0309
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Human Fecal Microbiota Transplantation into Mice Attenuates MPTP-Induced Neurotoxicity via AMPK/SOD2 Pathway

Abstract: Increasing evidence has shown that gut dysbacteriosis may play a crucial role in neuroinflammation in Parkinson's disease (PD). However, the specific mechanisms that link gut microbiota to PD remain unexplored. Given the critical roles of blood-brain barrier (BBB) dysfunction and mitochondrial dysfunction in the development of PD, we aimed to evaluate the interactions among the gut microbiota, BBB, and mitochondrial resistance to oxidation and inflammation in PD. We investigated the effects of fecal microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 82 publications
0
26
0
Order By: Relevance
“…Akkermansia, a beneficial gut bacterium, has demonstrated the ability to regulate immune response, reduce intestinal inflammation, and show promise in alleviating mental illnesses. Importantly, direct supplementation of Akkermansia has been linked to increased growth of Bifidobacterium ( 31 ) and a reduction in depressive and anxious behavior after chronic stress ( 32 ), potentially through the restoration of dopamine and BDNF levels or the modulation of AMPK ( 33 ) and PI3K/AKT signaling pathways to inhibit neuroinflammation through CREB ( 34 ). Additionally, Bifidobacterium and Butyricimonas can enhance the production of butyrate, an anti-inflammatory substance that impedes the entry of intestinal toxins into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia, a beneficial gut bacterium, has demonstrated the ability to regulate immune response, reduce intestinal inflammation, and show promise in alleviating mental illnesses. Importantly, direct supplementation of Akkermansia has been linked to increased growth of Bifidobacterium ( 31 ) and a reduction in depressive and anxious behavior after chronic stress ( 32 ), potentially through the restoration of dopamine and BDNF levels or the modulation of AMPK ( 33 ) and PI3K/AKT signaling pathways to inhibit neuroinflammation through CREB ( 34 ). Additionally, Bifidobacterium and Butyricimonas can enhance the production of butyrate, an anti-inflammatory substance that impedes the entry of intestinal toxins into the brain.…”
Section: Discussionmentioning
confidence: 99%
“…We cut the PVDF membrane while retaining sufficient width and length to allow different positions of the PVDF membrane to bond with different primary antibodies. Then blotted with primary antibodies for LC3 (1:1000, ab192890, Abcam) 54 , P62 (1:1000, ab109012, Abcam) 55 , SIRT3 (1:500, #5490, CST) 56 , SOD2 (1:1000, #13141, CST) 57 , acetylated SOD2 (1:1000, ab137037, Abcam) 58 and GAPDH (1:2000, 60004-1-Ig, Proteintech) 59 overnight at 4 °C. Then, incubate with the secondary antibody for 1.5 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…524 A substantial body of literature has demonstrated the potential of microbiome-based therapeutics in alleviating dopaminergic damage and motor deficits in PD mouse models. 217,261,321,393,492,525,526 Adjunctive probiotic administration was found to increase serum dopamine levels and improve motor function in PD patients receiving conventional regimen, compared to patients receiving conventional regimen alone. 491 Moreover, the administration of berberine has been shown to stimulate the production of dopa and dopamine in the gut microbiota by activating tyrosine hydroxylase and dopa decarboxylase.…”
Section: Serotoninmentioning
confidence: 98%
“…These effects are attributed to the reduction of glial activation, as well as the restoration of metabolite and neurotransmitter abnormalities. 217,[259][260][261] In addition, it was found that FMT from healthy human controls mitigated MPTP-induced dysbiosis and neurotoxicity in MPTPinduced mice, whereas FMT from PD patients exacerbated these pathologies. 261 Taken together, these findings corroborate the contributory roles of gut microbiota in driving glial activation and neuropathologies.…”
Section: Microbiota-gut-brain Axis In Neurodegenerative Diseases Inte...mentioning
confidence: 99%